Effect of the use of probiotic Bacillus subtilis (QST 713) as a growth promoter in broilers: an alternative to bacitracin methylene disalicylate - Rivera-Perez, Walter (2021)
The global poultry trend toward the more responsible use of antibiotics is becoming recurrent and has demanded the need to generate new natural alternatives. Probiotics have gained importance as an option to use as growth promoters. This study aimed to evaluate Bacillus subtillis QST713 as a substitute for an antibiotic growth promoter (BMD). A total of 150 male broilers were assigned to three dietary treatments: 1) control diet (CO), 2) control diet + 500 g/t of BMD (AGP), and 3) control diet + 100 g/t of B. subtilis QST713 (PB), respectively. Each treatment was monitored for 5 wk for the productive variables: body weight, accumulated feed consumption, food conversion, and European efficiency factor. At the end of each week, fresh fecal samples were cultured and quantified for E. coli, Enterococcus spp., and Lactobacillus spp. At the end of the trial, blood samples were analyzed for hemogram and intestinal samples (anterior portion) for histomorphometry. The data were statistically analyzed with an analysis of variance and subjected to a least significant difference test (Tukey). The zootechnical yields were similar in the AGP and PB groups (P ˃ 0.05); both superior to the control group. In the hematological profiles, no difference was observed between the experimental groups. E. coli and Enterococcus counts were significantly lower (P ˂ 0.05), and Lactobacillus counts were significantly (P ˂ 0.05) higher in the PB group, relative to CO and AGP groups. No differences (P ˃ 0.05) were found in bacterial counts between the CO and AGP groups. The intestinal mucosa and villi in the PB group were significantly (P ˂ 0.05) longer and with less deeper crypts than CO and AGP groups. We conclude that B. subtillis QST713, used at the suggested commercial dose (100 g/ton), is an effective growth-promoting alternative to BMD that modulates the microbiota and intestinal architecture, thus producing zootechnical yields consistent with BMD.